Functional assessment of mother-child relationships: The EEI Scale - Panduro Paredes, José Antonio (1998)
An infant stimulation in mother-child relationship assessment scale (ISA Scale) was developed, based on a classification of probable effects on child's behavior, such as behavioral promotion stimulation (BPS) and behavioral control stimulation (BCS), refering to mother action level to promote desirable behaviors and to control socially non desirable behaviors in child's behavior repertory. 540 mother-child dyads were evaluated. The construct validity tests showed significant correlations in item analysis, between subescales along with child development measures (social maturity and aggressiveness). In addition significant correlations (p<.05) were identified in validity tests showing criteria. On the other hand, the reliability tests indicated high stability and internal consistency. During this work we verified the important influence this stimulation had on the psychological development of the child.